1. The value of trace minerals in a wintering and fattening ration. 2. Self-feeding grain in dry lot versus self-feeding on bluestem pasture. - Baker, F.H.; Smith, E.F.; Menzies, C.S.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Thirty choice Hereford steer calves, 10 head to a lot, are being used. Eight steers of each lot were obtained in a shipment from the Lanker Ranch near Medicine Lodge, Kan. The remaining two steers of each lot were obtained from the Currie Ranch near Westmoreland, Kan. The system of management planned for each lot of steers follows: Lot 15-Wintored on sorghum silage, 4 pounds of grain, and 1 pound of 41 percent protein concentrate per head daily, free access to mineral (bone meal and salt) and salt; bluestem pasture May 1 to August 1; self-fed grain on bluestem pasture after August 1 to choice grade. Lot 10-Wintered on sorghum silage, 4 pounds of grain, and 1 pound of protein concentrate per head daily, free access to mineral (bone meal and salt) and salt; grazed on bluestem pasture May 1 to August 1; self-fed grain in dry lot after August 1 -to choice:) grade. Lot 9-Wintered on sorghum silage, 4 pounds of grain, and 1 pound of protein concentrate per head daily; free access to mineral (bone meal and salt) and salt; grazed on bluestem pasture, May 1 to August 1; self-fed grain in dry lot from August 1 until they grade choice. Trace minerals are being supplied to this lot of steers during the wintering and fattening phases of the test.
Keywords: Beef; Trace minerals; Dry lot vs. Bluestem pasture; Gain